1986
DOI: 10.1084/jem.164.2.594
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 of the central nervous system is produced by ameboid microglia.

Abstract: By screening specific populations of rat brain cells, we found that ameboid microglia secrete an 18 kD peptide with IL-1 biological activity. The IL-1 activity released by microglia was found to be identical to rat macrophage IL-1 on fractionation by gel filtration and high pressure liquid anion-exchange chromatography, and it was neutralized by an antiserum specific for murine IL-1. When added to astroglia grown in culture, microglial IL-1 increased the cell number of five- to sevenfold, and increased astrogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
283
2
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 803 publications
(299 citation statements)
references
References 32 publications
13
283
2
1
Order By: Relevance
“…Cytokines, neuronal, and glial markers in central structures As described previously after nerve injury (Hains et al, 2004;Verge et al, 2004), we observed microglia activation in both SN-CCI and IoN-CCI rats with a concomitant upregulation of IL-1␤ mRNA levels, supporting the idea that IL-1␤ is produced by ameboid microglia (Giulian et al, 1986;Ferrari et al, 1997). Activated microglia is a key feature of pain hypersensitivity, and recent data have shown that its blockade prevents development of allodynia-like behavior in animal models of neuropathic pain (Raghavendra et al, 2003;Ledeboer et al, 2005;Piao et al, 2006).…”
Section: Cytokines Neuronal and Glial Markers In Sensory Gangliasupporting
confidence: 66%
“…Cytokines, neuronal, and glial markers in central structures As described previously after nerve injury (Hains et al, 2004;Verge et al, 2004), we observed microglia activation in both SN-CCI and IoN-CCI rats with a concomitant upregulation of IL-1␤ mRNA levels, supporting the idea that IL-1␤ is produced by ameboid microglia (Giulian et al, 1986;Ferrari et al, 1997). Activated microglia is a key feature of pain hypersensitivity, and recent data have shown that its blockade prevents development of allodynia-like behavior in animal models of neuropathic pain (Raghavendra et al, 2003;Ledeboer et al, 2005;Piao et al, 2006).…”
Section: Cytokines Neuronal and Glial Markers In Sensory Gangliasupporting
confidence: 66%
“…Microglia usually act to eliminate microorganisms and deleterious debris and may be involved in neuroprotection by producing neurotrophic factors [9,41]. Microglia also have a cytotoxic function because they release reactive oxygen species, nitric oxide, or inflammatory cytokines; these released factors produce immunological actions and act on neurons to alter their function [2,4,8,10,11,23,40,43]. NSAIDs might affect the SC indirectly through signals from the DRG or direct suppression of cytokines expression in spinal microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-1 family cytokines consist of six principle, related family members, i.e., three receptor ligands (IL-1α, IL-1β and IL-1 receptor antagonist (IL-1Ra)), two receptor subtypes (IL-1RI and IL-1RII) and an accessory protein (IL-1AcP) (Dinarello, 1996). These IL-1 family inflammatory mediators show cell-specific patterns of production, expression and release since ligands are made principally by glia (and some neurons) while astrocytes and neurons express the signal transducing IL-1 receptor, IL-1RI (Ban et al, 1991(Ban et al, , 1993Fontana et al, 1982;Giulian et al, 1986;Lechan et al, 1990). In addition, neurons (and glia) can be differentially distributed between and within various brain regions (Dombrowski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%